2013
DOI: 10.1177/0267659113479816
|View full text |Cite
|
Sign up to set email alerts
|

Blood conservation strategies reduce the need for transfusions in ascending and aortic arch surgery

Abstract: The aggressive use of a comprehensive blood conservation strategy in ascending and aortic arch surgery can significantly reduce the need for blood transfusions and is associated with less postoperative morbidity. Further evaluation with a randomized, controlled trial is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Cambria et al 27 found that PRBC transfusion was one of the independent risk factors for mortality in patients undergoing thoracoabdominal surgery (OR, 1.4; 95% CI, 1.1-1.7; p ¼ 0.005). Chu et al, 6 in their evaluation of transfusion practices, found that the patients in the blood conservation group did indeed have less blood transfused, and had lower morbidity than the control group. However, a difference in mortality was not seen.…”
Section: Blood Transfusion In Aortic Surgerymentioning
confidence: 99%
“…Cambria et al 27 found that PRBC transfusion was one of the independent risk factors for mortality in patients undergoing thoracoabdominal surgery (OR, 1.4; 95% CI, 1.1-1.7; p ¼ 0.005). Chu et al, 6 in their evaluation of transfusion practices, found that the patients in the blood conservation group did indeed have less blood transfused, and had lower morbidity than the control group. However, a difference in mortality was not seen.…”
Section: Blood Transfusion In Aortic Surgerymentioning
confidence: 99%
“…Cambria et al 27 found that PRBC transfusion was one of the independent risk factors for mortality in patients undergoing thoracoabdominal surgery (OR, 1.4; 95% CI, 1.1-1.7; p ¼ 0.005). Chu et al, 6 in their evaluation of transfusion practices, found that the patients in the blood conservation group did indeed have less blood transfused, and had lower morbidity than the control group. However, a difference in mortality was not seen.…”
Section: Blood Transfusion In Aortic Surgerymentioning
confidence: 99%
“…Complex aortic reconstruction, urgent presentations, multiple suture lines, prolonged CPB, and hypothermia account for the higher risk. 6 Unsurprisingly, there is a greater likelihood of exposure to blood products. 2,13 Nevertheless, most studies have excluded this group of patients from their analysis, and consequently, current transfusion guidelines are based on literature addressing nonaortic procedures.…”
Section: Blood Transfusion In Aortic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodilution attenuates the adverse effects of hypothermia during cardiopulmonary bypass (CPB) on tissue perfusion [1]. While the priming volume of the bypass machine circuit provides hemodilution, acute normovolemic hemodilution is used to protect some portion of the patient's blood and to reduce need for packed blood products [2,3]. We present a case, where in our opinion; the whole blood collected from the patient caused premature coagulation in the bypass pump circuit.…”
mentioning
confidence: 97%